STATE OF DEVELOPMENT OF VEGETABLE GROWING AND PRESERVATION OF INNOVATIVE AGRICULTURAL PRODUCTION AS A VECTOR OF EFFECTIVE MANAGEMENT - Пономарьова, Марина; Должикова, Ірина; Фоменко, Владислава (SWorldJournal, 2022)
The paper presents the results of a study of the management of innovative activities of the enterprise in vegetable growing. Theoretical, methodical aspects of management of innovative activity of the enterprise in vegetable growing are opened. The theor